2019
DOI: 10.1021/acs.biomac.9b00539
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Liposomes with Hydrophilic Polymers Results in Macrophage Uptake Independent of the Protein Corona

Abstract: Liposomes are established drug carriers that are employed to transport and deliver hydrophilic drugs in the body. To minimize unspecific cellular uptake, nanocarriers are commonly modified with poly(ethylene glycol) (PEG), which is known to minimize unspecific protein adsorption. However, to date, it has not been studied whether this is an intrinsic and specific property of PEG or if it can be transferred to hyperbranched polyglycerol (hbPG) as well. Additionally, it remains unclear if the reduction of unspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 55 publications
1
60
0
Order By: Relevance
“…Since most single proteins in blood plasma are in the size range of 6–10 nm, [ 55 ] thus smaller than the investigated nanoparticles, they are eluting prior to the nanoparticles in the AF4 channel (Figure 2). [ 19,26 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since most single proteins in blood plasma are in the size range of 6–10 nm, [ 55 ] thus smaller than the investigated nanoparticles, they are eluting prior to the nanoparticles in the AF4 channel (Figure 2). [ 19,26 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these results further indicate that there is no major adsorption of proteins on the nanoparticles leading to a significant size increase of the complexes, which is in accordance to findings on liposomes as determined by AF4. [ 19 ] On the other hand, a previous study with solid nanoparticles demonstrated corona formation induced changes in particle size as detected by dynamic light scattering (DLS) or retention time shifts in AF4. [ 26 ] This is in agreement with a recent study from Couffin and coworkers, which proved that with AF4 it is possible to detect small size differences (5–10 nm) between different nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations